Electrolyte Effect on Electrochemically Controlled Polymerizations - Hern, Zachary C.; Massad, Ramzi N.; Diaconescu, Paula L. (Synthesis, 2025)
Electrochemically controlled redox-switchable polymerization uses an electric potential to bias the monomer selectivity of a catalyst. Many ferrocene-appended catalysts can exist in two oxidation states, a neutral reduced state and an oxidized cationic state. Electrochemical generation of the oxidized cationic state produces a charged species whose counteranion is determined by the identity of the supporting electrolyte anion. Herein, the role the counteranion has on monomer selectivity and polymerization kinetics is investigated. Minimal differences in monomer selectivity in the reduced state was found, however, in the oxidized state, the coordinating ability of the counteranion greatly influenced the rate of polymerization. How activity differences governed by the choice of electrolyte can be utilized to access desired diblock copolymers is also described.
Keywords: redox-switchable catalysis; electrochemistry; ring-opening polymerization; organometallic chemistry